Thermal stability and light transmission capability of nano TiO2 enhanced phase change material as thermal energy storage - Rosli, M. Arif Fikri; Pandey, A. K.; Samykano, M.; Sharma, Kamal; Selvaraj, Jeyraj; Abd Rahim, Nasrudin; Saidura, R. (IOP Publishing, 2021)
InPhase Change Material (PCM) already pick up some interests among recent researchers and engineers due to its unique characteristic of storage and releasing high quantity of heat energy during phase transition process. However, there's some disadvantages for this material such as low absorption of irradiance and super cooling phenomena occurred. To overcome this problem high conductive nanoparticles are dispersed in to the PCM resulting a new composite called nano-enhanced PCM (NEPCM). In this present paper, the impact of adding Titanium (IV) oxide nanoparticles (TiO2) on pure paraffin wax also was investigated. Output reveal that NEPCM have greater thermal stability than pure PCM. When increasing the %wt, the thermal stability also increases, as shown clearly when using Sodium Dodecylbenzene Sulfonate (SDBS) as surfactant.